The Role of Youth in the Creation of the Enlightened Society "New Uzbekistan". - Yusupov Arabboy Bahodirjon son; Xakimov Pakhlavon Jaloldin son; Rayimov Asadbek Rivojiddin son; Mahmudov JavohirNe'matjon son (Periodica Journal, 2022)
This article, training receiving students only own fields mature experts, but high spiritual, creative, athletic, intelligent and patriot student the role of our country in the development and prosperity of our country, what we can do for the next generation, create better opportunities for the youth in the current era, the goals of our youth to prosper.
Keywords: Universality; culture; worldview; enthusiasm